Analysis of Visitors' Multisensory Experiences Towards Mental Health Benefits in Outdoor Destinations - Ratna Roostika; Rizqi Adhyka Kusumawati; Punik Mumpuni; Titik Kuntari (Business Management Analysis Journal (BMAJ), 2025)
This study explores the increasing trend of traveling outdoors after the COVID-19 pandemic. There is still limited research in Indonesia exploring the role of multisensory experiences on tourists’ mental health benefits. Two main theories are used “the Attention Restorative Theory (ATR) and the Theory of Grounded Cognition, as the basis for developing the research model. This study aims to analyze the impact of the multisensory experience of outdoor tourism on place attachment, the perception of environmental restoration, and the perception of mental health benefits. This study examined 278 respondents who visited city parks and outdoor tourist sites in Yogyakarta and its surroundings. Using quantitative approaches and PLS statistical tools, it was found that the influence of multisensory experiences affects place attachment, perception of environmental restoration, and mental health benefits. The perception of environmental restoration also affects the mental health benefits. Only place attachment does not affect the mental health benefits of visiting outdoor destinations. The implication for marketing strategies is that tourism should be designed to provide mental health benefits or balance between physical and mental health.